2001
DOI: 10.1046/j.1468-3083.2001.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Blue naevus with satellitosis mimicking malignant melanoma

Abstract: Blue naevus is an acquired benign melanocytic naevus. It is a firm, sharply defined dark blue to grey-black papule or nodule, which is likely to arise from the arrested dermal melanocytes in the dermis. In the last few years, blue naevus has attracted much attention due to the recognition of new entities and to its confusion with malignant melanoma. We report a 69-year-old man who developed a blue-black nodular lesion with satellitosis on his scalp. Although clinically it was thought to be a malignant melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…However, in a very small number of cases [1, 2, 3, 4, 5, 6], including our case, a blue nevus can be accompanied by satellite lesions. This is when the physician needs to differentially diagnose it from malignant melanoma, especially the nodular type.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, in a very small number of cases [1, 2, 3, 4, 5, 6], including our case, a blue nevus can be accompanied by satellite lesions. This is when the physician needs to differentially diagnose it from malignant melanoma, especially the nodular type.…”
Section: Discussionmentioning
confidence: 66%
“…Malignant blue nevus is rare, and a common blue nevus rarely needs a differential diagnosis from malignant melanoma. Although a melanocytic nevus with a satellite lesion is usually suggestive of a peripherally disseminating malignant melanoma, very few cases of blue nevus with satellite lesions have been reported thus far [1, 2, 3, 4, 5, 6]. To our knowledge, this is the seventh case of a blue nevus with satellitosis.…”
Section: Introductionmentioning
confidence: 79%
“…Sahin et al 18 reported a patient presenting a blue to black nodule with satellites on the scalp clinically resembling melanoma. Dermoscopic examination revealed a homogenous blue pigmentation leading to the correct diagnosis of blue nevus with satellites, as confirmed histopathologically.…”
Section: Discussionmentioning
confidence: 99%
“…There have been five cases of blue nevus with satellitosis reported to date (7,(11)(12)(13)(14). Table 1 shows the Table 1 -Demographic characteristics of previously reported cases of blue nevus with satellitosis (7,(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%